2021
DOI: 10.1101/2021.01.18.427131
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Three-dimensional synaptic organization of layer III of the human temporal neocortex

Abstract: In the present study we have used Focused Ion Beam/Scanning Electron Microscopy (FIB/SEM) to perform a study of the synaptic organization of layer III of Brodmann’s area 21 in human. We analyzed the synaptic density, 3D spatial distribution, and type (excitatory/inhibitory), as well as the shape and size of each synaptic junction of 4945 synapses that were fully reconstructed in 3D. Moreover, the postsynaptic targets of 1888 synapses were determined. We also compared several electron microscopy methods and ana… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
27
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 102 publications
(230 reference statements)
8
27
0
Order By: Relevance
“…In addition, the majority of the synapses that a pyramidal cell receives are on spines and they represent the vast majority of AS synapses (DeFelipe and Fariñas, 1992). In the human transentorhinal cortex, 75% of the synapses were AS on spines, which is similar to the case of the AS found in the layer III of the temporal cortex (75%) using the same analysis method (Cano-Astorga et al, 2021). This percentage was much higher in the CA1 hippocampal field, as high as 94% in the superficial part of the CA1 stratum pyramidale (Montero-Crespo et al, 2020).…”
Section: Postsynaptic Targetssupporting
confidence: 56%
See 1 more Smart Citation
“…In addition, the majority of the synapses that a pyramidal cell receives are on spines and they represent the vast majority of AS synapses (DeFelipe and Fariñas, 1992). In the human transentorhinal cortex, 75% of the synapses were AS on spines, which is similar to the case of the AS found in the layer III of the temporal cortex (75%) using the same analysis method (Cano-Astorga et al, 2021). This percentage was much higher in the CA1 hippocampal field, as high as 94% in the superficial part of the CA1 stratum pyramidale (Montero-Crespo et al, 2020).…”
Section: Postsynaptic Targetssupporting
confidence: 56%
“…Finally, the present results indicate that the distribution of synapses in the neuropil of both control and AD samples is nearly random, only constrained by the fact that synapses cannot physically overlap in space and so their geometric centers or centroids cannot be too close to their neighbors. As we have previously shown in human brain samples from hippocampal CA1, entorhinal cortex, transentorhinal cortex and temporal cortex, there seems to be no limitation to the position of any synapse except the space already occupied by other synapses (Montero-Crespo et al, 2020;Domínguez-Álvaro et al, 2018Domínguez-Álvaro et al, , 2021Cano-Astorga et al, 2021). Previous studies in the plaque-free neuropil of AD cases also showed a random distribution pattern of the synapses in other brain regions (Blazquez-Llorca et al, 2013, Domínguez-Álvaro et al, 2018Montero-Crespo et al, 2021).…”
Section: Synaptic Density Proportions and Spatial Distributionmentioning
confidence: 63%
“…In order to compare their selection of output synapse locations to the distribution of potential GABAergic synaptic target sites in the neuropil, we have studied the distribution of GABAergic synapses on dendritic spines and shafts in layer III. Using post-embedding immunogold reactions with antibodies to GABA in electron-microscopic sections (Somogyi & Soltész, 1986) and a stereological method based on 3D tracing of synapses and their targets in a defined volume through serial sections (West, 1999; Cano-Astorga et al, 2021) we determined the numerical density and the proportion of GABAergic synapses and their neuropil targets in samples from temporal and frontal cortices.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, the reduction in spinous synapse areas in CA1 and dlPFC of monkeys exposed to neonatal anesthesia implies an enduring loss of excitatory synapse coverage with specific long-term consequences for the makeup of excitatory receptors, and by extension excitatory neurotransmission, in both regions. Almost all (91-99%) spinous synapses in the CA1 and cortex of rodents and primates are excitatory, as demonstrated by their asymmetry (Blazquez-Llorca et al, 2021; Cano-Astorga et al, 2021; Domínguez-Álvaro et al, 2019; Hsu et al, 2017; Montero-Crespo et al, 2020; Santuy et al, 2018; Tao et al, 2018). Thus, the reductions in spinous synapse areas by early-life anesthesia in the present cohort of monkeys are likely highly specific to excitatory synapses.…”
Section: Discussionmentioning
confidence: 99%